The Relationship Between Uterine Artery two-dimensional Color Doppler Measurement and Pregnancy Outcome: A Prospective Observational Study - S Prasad; R Goyal; Y Kumar; P Nayar; S Hajela; A Kumaran; R Vairagi; Sh Chauhan (JRI, 2017)
Background: The purpose of the study was to evaluate the role of uterine blood flow parameters measured by uterine artery two-dimensional (2D)-power color doppler (PCD) ultrasound in predicting fertility outcomes in women undergoing IVF-ET cycles. Methods: In this prospective observational study, a total of 188 infertile women who underwent IVF-ET cycles were investigated. Uterine artery 2D-PD measurements were taken during early follicular phase and on day of trigger. Pulsatility Index (PI), Resistant Index (RI), Peak Systolic Velocity (PSV), and Systolic/Diastolic ratio (S/D) were measured. Statistical correlation was sought between the doppler parameters and fertility outcomes. Results: The pregnancy rate was 40.43% (76/188). The women who conceived (n=76) (Group A) were found to have mean age of 31.2±3.9 years whereas the non-pregnant group of women (n=112) (Group B) had mean age of 31.45±4.25 years. The mean PI measurements subsequently during early follicular phase and on the day of hCG trigger between group A and group B were comparable (2.09±1.15 versus 1.9±0.95; p=0.385 and 1.86±1.12 versus 2.03±1.0; p=0.192, respectively). No significant changes in the uterine artery PSV values and S/D values and RI were noted during the cycle. Conclusion: Uterine artery doppler evaluation in women undergoing IVF cycles was not predictive of the pregnancy outcomes.